Caracterização de ZnSe crescido por CVT para aplicação como bolômetro cintilante - Raphaela de Oliveira Gonçalves (2020)
In this work, three groups with different stoichiometric ratios of ultra-pure non-enriched and non-luminescent polycrystalline zinc selenide samples grown by the chemical vapor transport method (CVT) are characterized. The work aimed to make the samples luminescent for application of the material as a scintillating bolometer. The scintillating bolometric detection technique has been used in experiments that search for neutrinoless double beta decay of 82Se - predicted in extensions of the Standard Model and that carries important information about the nature of neutrinos and their mass scale. Electron paramagnetic resonance and photoluminescence were the principal techniques chosen for the characterization of the samples in this work. The samples were subjected to thermal treatments, irradiation by gama and particle radiation, as well as doping processes with aluminum and gallium by diffusion and ion implantation. The results of the work demonstrate that no process that does not introduce impurities into the material is capable of making it strongly luminescent/scintillating. Since the complexed defects involving donor impurities and zinc vacancies (A-centers) are associated with the luminescence characteristic bands of the material in the yellow-red region according to the literature, it was possible to infer that these defects are the most efficient centers of radiative recombination in zinc selenide. However, it was also observed that the introduction of impurities in low concentrations is already sufficient to make the material visibly luminescent. Thus, its application as a scintillating bolometer is not compromised, since the low detection background achieved with the technique can be easily maintained by corrections, once the impurity (and the concentration) that will be introduced into the material to optimize its luminescence is known.